Adil Berpoligami: Analisis Hukum Keluarga Islam Di Indonesia - Fatimah Zuhrah (Pascasarjana IAIN Metro, 2017)
Polygamy is a necessity in Islam. The basic principle of polygamy is the element of justice. One of the factors shows justice in clothing, food, planks and mu'amalah between his wife. The justice of love and affection will not be able to be fair. So a husband keeps himself, not too much with one of his wives. This can be seen in the historical fact that prophets, companions, tabi'in and many Muslims who practice polygamy, so that a man capable of doing justice in polygamy is a man who has goodness in goodness, this is personal and common to the wider community.As for people who argue that polygamy is forbidden because it sees the impossibility of justice in polygamy. The polygamic justice in Islam is limited in three ways, the first is the number, the second is the livelihood and the third is justice between the wives. In principle, the two verses above consider that the principle of marriage is polygamy and an exception to monogamy. But by the rule that al- ashlu dâ'iman yuqoddamu al-istitsnâ '. The point is that istitsn 'always takes precedence over principle, because the exception is reinforcement.